Effect of surface active agent on thermal properties of carbonate salt/carbon nanomaterial composite phase change material. (15th October 2015) - Tao, Y.B.; Lin, C.H.; He, Y.L.
Highlights: Nanomaterial aggregation weakens CPCM thermal performance. Larger nanomaterial specific surface area, worse CPCM thermal performance. SDS is a better SAA due to the less solid decomposition products. The 10 or higher mass ratio of SDS to nanomaterial is recommended. Thermal conductivity of CPCM can be enhanced 58.75%. Abstract: Surface active agent (SAA) was used to improve nanomaterial dispersion during preparation process of carbonate salt/nanomaterial composite phase change material (CPCM) by solution evaporation method. In order to investigate the effects of SAA on CPCM thermal performance, three kinds of PCM samples were prepared and their thermal performances were characterized. The results show that nanomaterial dispersion greatly affects CPCM thermal performance. For CPCM without SAA, its thermal performance is weakened instead of enhanced due to nanomaterial aggregation and the weakening phenomenon is more obvious when nanomaterial has larger specific surface area. SAA decomposes during high temperature CPCM working process. And the effect of SAA on CPCM thermal performance has duality: on the positive side, SAA can improve nanomaterial dispersion and enhance CPCM thermal performance; on the negative side, SAA decomposition products may weaken CPCM thermal performance. So, SAA and its mass fraction should be carefully selected. Sodium dodecyl sulfate (SDS) is a better SAA for high temperature nano-CPCM and a high mass ratio of SDS to nanomaterial is recommended. With mass ratio of SAA to nanomaterial 10:1, PCM thermal conductivity can be enhanced up to 58.75% by adding 1 wt.% multi-walled carbon nanotubes.